Post-operative Appendix Specimen Retention Presenting as Small Bowel Obstruction - Tiffany Proffitt; Kristen Whitworth; Christopher Trigger (Clinical Practice and Cases in Emergency Medicine, 2017)
One rare complication of appendectomy is a retained appendicolith, which can become a focal point for infection presenting hours to years after surgery. We present a case in which a 50-year-old male presented to the emergency department with a small bowel obstruction one week post appendectomy. A diagnostic laparoscopy was performed, and a necrotic appendiceal specimen containing a staple line across the base as well as an appendicolith was removed. It is crucial to include rare surgical complications in our differentials, alongside the more common pathologies when approaching and treating patients with abdominal pain.